The Application of Spatial Analysis Methods in the Real Estate Market in South‑Eastern Poland - Dejniak, Dorota (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The aim of the article is to apply the method of spatial analysis to research the real estate property market in south‑eastern Poland. The methods of spatial statistics will be used to model the space differences of prices per one square metre of dwelling surface located in districts of south‑eastern Poland and to investigate spatial autocorrelation. The databases will be presented in a graphical form. The results may be used to set the spatial regularities and relations. The methods presented may be applied while making strategic decisions.